2003
DOI: 10.1034/j.1600-0609.2003.00071.x
|View full text |Cite
|
Sign up to set email alerts
|

Safety monitoring of cardiac and hepatic systems in β‐thalassemia patients with chelating treatment in Taiwan*

Abstract: We conducted a prospective 3-yr clinical study comparing deferiprone (L1) with desferrioxamine (DFX). The therapeutic efficacy and potential side-effects on cardiac and/or hepatic systems of thalassemia patients were assessed by left ventricular ejection fraction, T2-weighted magnetic resonance imaging, and biochemical parameters. In both groups, levels of serum ferritin decreased significantly, and the hepatic function improved notably. Besides decrement of iron, no marked pathohistological changes were obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 38 publications
4
41
0
1
Order By: Relevance
“…Results of randomized clinical trials comparing DFO with DFP demonstrated no difference after 12 months of treatment in serum ferritin levels or liver iron concentration [23,24]. Similar results have been obtained in other studies [25,26,27]. …”
Section: Dfp Efficacysupporting
confidence: 76%
See 1 more Smart Citation
“…Results of randomized clinical trials comparing DFO with DFP demonstrated no difference after 12 months of treatment in serum ferritin levels or liver iron concentration [23,24]. Similar results have been obtained in other studies [25,26,27]. …”
Section: Dfp Efficacysupporting
confidence: 76%
“…In two studies, DFP at 75 mg/kg/day was as effective as DFO at 50 mg/kg/day for 5–6 days per week at reducing cardiac iron by MR signal intensity ratio [24,32]. Peng et al [27] compared cardiac iron, estimated by MR signal intensity and LVEF over 3 years in 13 patients taking DFO (50 mg/kg/day at least 5 days per week) with 11 patients taking DFP (75 mg/kg/day). Cardiac iron was markedly improved in 5 patients on DFP but only in 2 patients on DFO treatment.…”
Section: Dfp Efficacymentioning
confidence: 99%
“…The incidence of fluctuation of hepatic transaminase levels after deferiprone exposure found in our Thai patients seemed to be higher than Caucasian population [21,42,54] but somewhat similar to Chinese patients [41,59]. Around 50% of the incidences were mild and transient; patients could continue on the study drug without interruption.…”
Section: Discussionsupporting
confidence: 54%
“…The researchers found no progression of hepatic fibrosis or increased liver iron stores in most patients with deferiprone treatment [46]. Another Taiwanese study group conducted a prospective 3 year study comparing cardiac and hepatic efficacy and safety of chelating treatment with deferiprone and deferoxamine [47]. Among 24 patients studied, 11 were switched from deferoxamine to deferiprone due to unwillingness or intolerability while the remaining 13 patients stayed on deferoxamine.…”
Section: Clinical Experiencementioning
confidence: 97%
“…There was a marginal benefit in reducing cardiac iron accumulation and increasing cardiac function in the deferiprone group. The study group hence recommended the use of deferiprone in patients who failed on deferoxamine treatment [47].…”
Section: Clinical Experiencementioning
confidence: 99%